Cervical vertebrae anomalies in orthodontic patients: a growth-based superimpositional approach. - Koletsis, Despina D; Halazonetis, Demetrios J (Eur J Orthod, 2010)
The purpose of this study was to propose a growth-based structural superimposition method for assessment of cervical vertebral fusion and evaluate variations and abnormalities of the upper cervical vertebrae. Standardized lateral cephalograms of 156 patients (69 males and 87 females, age range 6-20 years), representing a skeletally heterogeneous orthodontic population, were used. Primary criterion for sample selection was the existence of at least two lateral cephalograms, one taken before orthodontic treatment, which depicted the first four cervical vertebrae. The abnormalities of the vertebrae were estimated by visual assessment and structural superimposition. Lateral cephalometric analysis was conducted in order to correlate vertebral anomalies to skeletal pattern. Descriptive statistics were calculated for all variables and interobserver agreement was evaluated using the kappa statistic. Four patients (2.6 per cent) were found to have secondary ossicles in close relationship to the first cervical vertebra, while in 7.4 per cent, the vertebral arteries of the atlas were surrounded by a complete ring-shaped osseous structure. Three cephalograms showed atlas posterior arch dehiscence. After visual examination, 14 patients were provisionally identified as presenting fusion between the second and third cervical vertebrae. However, growth-based superimposition of the radiographs disclosed that no patient showed actual fusion, even though the lateral cephalometric analysis revealed sufficient extreme skeletal patterns, which have been previously related to vertebral fusion. The findings of this study demonstrated a low percentage of atlas anomalies. It was not possible to correlate skeletal pattern to fusion of cervical vertebrae because no fusions were found. Subjective visual examination of a single cephalogram may result in false-positive findings of fusion and growth-based superimposition is recommended.
Keywords: Adolescent; Cephalometry; Cervical Atlas; Cervical Vertebrae; Child; Female; Humans; Longitudinal Studies; Male; Malocclusion; Radiography; Spinal Diseases; Young Adult